IT Project Management Control and The Control Objectives for IT and Related Technology COBIT 2019 Framework - Jaya, Ruddy Kusuma; Melissa Indah Fianty (The Indonesian Journal of Computer Science, 2023)
The development of information technology has been leveraged by state-owned enterprises (BUMN) operating in the fields of Maintenance, Repair, and Overhaul, as well as industrial services in Indonesia. Among the company's 21 priority projects, three projects have been identified as experiencing delays in the planning phase related to the delivery of business requirements. The measurement of IT governance capability was conducted using the process rating of COBIT 2019. The selected process objectives were APO02, APO03, and APO05. The results of the capability level measurement indicate that APO02, APO03, and APO05 have reached level 2. Based on the measurement results, findings have been identified that require improvement, especially in APO03, such as providing understanding to key stakeholders about enterprise architecture and enterprise architecture design. As a recommendation for improvement, it is expected that the company can engage in Enterprise Architecture design to align strategic program priorities with architectural objectives.